2022
DOI: 10.3390/jcm11071956
|View full text |Cite
|
Sign up to set email alerts
|

Seven COVID-19 Patients Treated with C-Reactive Protein (CRP) Apheresis

Abstract: Background: The fulminant course of COVID-19, triggered by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), presents with a high mortality rate and still lacks a causative treatment. C-reactive protein (CRP) has been shown to increase dramatically during the disease progression and correlates with deleterious outcomes. Selective CRP apheresis can reduce circulating CRP levels fast and effective. Methods: Seven hospitalized patients with documented severe COVID-19 progression, elevated CRP plasma l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…In line with the aggravating effects of human pCRP*/mCRP in animal models, recent clinical studies revealed a correlation between CRP concentration and cardiac infarct size (Ries et al , 2021 ), and clinical deterioration and harmful inflammatory responses in COVID‐19. Importantly, the therapeutic reduction of CRP levels by CRP‐apheresis was highly beneficial in these clinical settings (Ringel et al , 2021 ; Schumann et al , 2021 ; Torzewski et al , 2021 ; Esposito et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with the aggravating effects of human pCRP*/mCRP in animal models, recent clinical studies revealed a correlation between CRP concentration and cardiac infarct size (Ries et al , 2021 ), and clinical deterioration and harmful inflammatory responses in COVID‐19. Importantly, the therapeutic reduction of CRP levels by CRP‐apheresis was highly beneficial in these clinical settings (Ringel et al , 2021 ; Schumann et al , 2021 ; Torzewski et al , 2021 ; Esposito et al , 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Helical polypeptides with covalently attached (via a carbon‐based linker) PC molecules (Tegler et al , 2011 ), peptide mimetics (mw > 700 Da) (Kumaresan et al , 2013 ), and anti‐sense oligonucleotides (ASO) (Warren & Flaim, n.d. ) targeting CRP have been developed, with the latter reaching phase II clinical trials (ISIS‐329993 and ISIS‐353512, NCT01710852, NCT01414101, and NCT00734240; Warren et al , 2015 ). Furthermore, reducing circulating pCRP levels via CRP apheresis using PC‐linked resins is currently being investigated with promising initial results as an adjunct therapy to minimize cardiac injury in patients with myocardial infarction (Ries et al , 2019 , 2021 ) and COVID‐19 (Pepys, 2021 ; Ringel et al , 2021 ; Schumann et al , 2021 ; Torzewski et al , 2021 ; Esposito et al , 2022 ). The therapeutic approaches discussed above target general pCRP inhibition and reduction of circulating pCRP levels.…”
Section: Introductionmentioning
confidence: 99%
“…Very impressively, it was shown by Esposito et al [14] how beneficial the removal of CRP is in severe COVID-19. The treatments were performed within the CACOV registry to allow for scientific evaluation.…”
Section: Crp Triggers the Disposal Of Hypoxic And Ischaemic Cellsmentioning
confidence: 98%
“…Very impressively, Esposito et al [ 108 ] demonstrated the benefits of eliminating CRP in severe COVID-19. The therapy was administered as part of the C-Reactive Protein Apheresis in COVID (CACOV) registry to enable a scientific assessment in this setting (DRKS00024376).…”
Section: Crp Causes the Disposal Of Ischemic And Hypoxic Cellsmentioning
confidence: 99%